Unveiling the role of sex in the metabolism of indoxyl sulfate and apixaban - Pina-Beltran, Blanca; Dimitrov, Daniel; McKay, Nathalie; Giot, Matthieu; Zdráhal, Zbyněk; Potěšil, David; Pustka, Václav; Peinado-Izaguerri, Jorge; Sáez Rodríguez, Julio; Poitevin, Stéphane; Burtey, Stéphane (Scientific reports, 2025)
Chronic Kidney Disease (CKD) is associated with heightened risk of thrombosis. Prescription of anticoagulants is key to manage it; however, CKD patients have shown an increased risk of bleeding under anticoagulation therapy compared to non-CKD patients. We hypothesized that the sex could modify the metabolism of indoxyl sulfate (IS), a uremic toxin and Apixaban. Our intoxication model shows that higher doses of IS and apixaban accumulate in the plasma of female mice because of expression differences in efflux transporters and cytochromes in the liver, ileum and kidneys, when compared to males. Furthermore, we found that accumulation of apixaban in females contributes to increased bleeding. Transcriptional analysis of liver samples revealed elevated Sult1a1 but reduced Abcg2 and Cyp3a11 in female mice, while in the kidneys the expression rates of Oat1 and Oat3 were respectively lower and higher than those observed in males, potentially affecting drug clearance. Whole proteomics liver analysis confirmed the previous transcriptional results at the protein level and revealed that sex had a major influence in regulating both coagulation and drug metabolism pathways. Thus, our findings underline the need for inclusive clinical and preclinical trials to accurately reflect sex-specific metabolic variations, and to consider CKD-specific changes to optimize dosing, minimize side effects, and improve patient outcomes.